2016
DOI: 10.1073/pnas.1610541113
|View full text |Cite
|
Sign up to set email alerts
|

How the hydrophobic factor drives protein folding

Abstract: How hydrophobicity (HY) drives protein folding is studied. The 1971 Nozaki-Tanford method of measuring HY is modified to use gases as solutes, not crystals, and this makes the method easy to use. Alkanes are found to be much more hydrophobic than rare gases, and the two different kinds of HY are termed intrinsic (rare gases) and extrinsic (alkanes). The HY values of rare gases are proportional to solvent-accessible surface area (ASA), whereas the HY values of alkanes depend on special hydration shells. Earlier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 22 publications
(25 reference statements)
6
72
1
Order By: Relevance
“…The basic idea of present research agrees well with the space‐filling models reported by Baldwin and Rose for the hydration shells on linear alkanes and with the hemispheric water distribution around hydrophobic side chain of zwitterionic alanine . The clathrate‐like assumption, which may be considered a rough approximation of the true semi‐rigid water shell in the case of large solutes, may play a significant role in the case of small size hydrocarbons as suggested by Stillinger “one should keep in mind, however, that many interesting solutes have sizes below this range, so that convex cage statistics is indeed relevant to their solutions” …”
Section: Methodological Frameworksupporting
confidence: 89%
See 3 more Smart Citations
“…The basic idea of present research agrees well with the space‐filling models reported by Baldwin and Rose for the hydration shells on linear alkanes and with the hemispheric water distribution around hydrophobic side chain of zwitterionic alanine . The clathrate‐like assumption, which may be considered a rough approximation of the true semi‐rigid water shell in the case of large solutes, may play a significant role in the case of small size hydrocarbons as suggested by Stillinger “one should keep in mind, however, that many interesting solutes have sizes below this range, so that convex cage statistics is indeed relevant to their solutions” …”
Section: Methodological Frameworksupporting
confidence: 89%
“…Thermodynamic studies on the solubility of several hydrocarbons show positive free energy, negative enthalpy, large negative entropy and positive heat capacity. This thermodynamic signature has been explained by the presence of a dynamic hydration shell around nonpolar substances, which depends on the size and shape of the nonpolar solute . Because of the Δ Cp > 0, enthalpy and entropy of solution increase with the temperature and the water shell “melts.” The water shell implies that each water molecule does not act independently of its neighbors, but they are correlated through highly directional hydrogen‐bonds giving rise to the well‐known order of water molecules around a hydrocarbon.…”
Section: Methodological Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, this mutation did not cause an entropy‐driven destabilization, probably because it increased the water‐protein interactions without increasing the conformational space available to the denatured polypeptide because the hydrophobic side‐chains were larger than that of Ala. The interaction between water molecules and proteins could originate from both alkane–water interaction and water–protein hydrogen bonds . The enthalpy stabilization originating from improved water–protein interactions (or hydration) in the native state implies that the mutation of Ala 38 does not affect the hydration structure of the thermally denatured state, because otherwise, the enthalpy gain would be nil.…”
Section: Resultsmentioning
confidence: 99%